ANALISIS PERAN SAT RESKRIM POLRES SIDRAP DALAM OPERASI PEKAT LIPU 2024 - Tahir, Muh.; Muhiddin, Nurmiati; Thamrin, Asbullah; Akbar, Syaiful; Reza, Jamil (The Juris, 2025)
Sidrap Regency, as the rice barn of South Sulawesi, faces serious problems in the form of social diseases (PEKAT) such as gambling, drug abuse, and prostitution. Operation PEKAT Lipu 2024 is a strategic initiative taken by the Sidrap Police Criminal Investigation Unit to combat crime and improve public security. This study aims to: 1) To find out what functions and responsibilities are carried out by the Sidrap Police Criminal Investigation Unit in the PEKAT Lipu 2024 operation. 2) To find out the obstacles and strategies implemented by the Sidrap Police Criminal Investigation Unit in making the PEKAT Lipu operation a success. This research is empirical legal research with a case study approach. The research was located at the Sidrap Police Criminal Investigation Unit during the period August 2024 to February 2025. This qualitative data was obtained through interviews with related parties, namely the leaders and members of the Sidrap Police Criminal Investigation Unit who were actively involved in the PEKAT Lipu 2024 operation. The data obtained in this study were analyzed through content analysis and qualitative descriptive analysis. The results of the study show that: 1) The functions and responsibilities carried out by the Sidrap Police Criminal Investigation Unit in Operation PEKAT Lipu 2024 include law enforcement against criminal acts, prevention of social diseases, and increasing public awareness and participation in maintaining environmental security. 2) Obstacles faced in implementing this operation include social stigma, limited access to remote areas, and adaptation of criminals to police tactics. Strategies implemented to overcome these obstacles include increasing the number of personnel, training for members, a humanistic approach to the community, and developing a more accessible reporting system.